Kemampuan Berpikir Kreatif Matematis Siswa pada Budaya Tabut Melalui PJBL - Melandri, Marco; Risnanosanti, Risnanosanti; Syofiana, Mardiah (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to develop students' mathematical creative thinking skills in the process of making Tabut miniatures as learning objects at the junior high school level. The method used is descriptive qualitative with the Project-Based Learning (PjBL) approach, and data collection techniques through observation, documentation, and semi-structured interviews. The study was conducted at SMPN 03 Bengkulu Tengah with the research subjects being class IX-A students. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the Project-Based Learning (PjBL) approach in making Tabut miniatures can develop students' mathematical creative thinking skills. The conclusion is that the Project-Based Learning (PjBL) approach can develop students' mathematical creative thinking skills through making Tabut miniatures. Keywords: Mathematical Creative Thinking, Pjbl, Tabut